Mechanical Properties of Layered-Carbon Fiber Reinforced with Vacuum Infusion Process - Ali Saifullah; Mohammad Jufri; Dini Kurniawati; Risky Chandra (University of Muhammadiyah Malang, 2021)
Research on material engineering is widely developed in the precursors, composition of the material, and technique to create a composite. The layering and vacuum infusion resin are the developing technology to create the composites with the new characteristics and properties. This experiment is intended to find out the characteristics of layering carbon fiber reinforced by resin and is molded with vacuum infusion technique. The specimens of this experiment is layered-carbon fiber composites determined in three, four, five, six, and seven layers. The precursors of 220 and 240 carbon fibers are the main material of the composites. The tests conducted to the specimens are bending and tensile tests. The both tests are treated to reveal the mechanical properties of the composites. The least layers of 220 and 240 carbon fiber result the highest value of bending test, but the most number of carbon fiber layers show the opposite value. The results are reverse in the tensile test. The highest value of the tensile test is achieved by the most layers of carbon fiber, while the lowest value is in the least layers. This result is almost the same with the strain-stress, but overall the graphic is similarly increase to the most layers. Deduction achieved in this experiment is that the number of layers in the carbon fiber composites is significantly influencing the mechanical properties of the composite.